Patterns of Bullying Behavior in Undergraduate Nursing Student - Natalia Elisa Rakinaung (GLOBAL HEALTH SCIENCE GROUP, 2023)
Bullying behaviour patterns among undergraduate nursing students are a worrying problem that can negatively affect the classroom, student well-being, and the standard of patient care. The study investigated the patterns of bullying behaviour in undergraduate nursing students. This observational study was conducted with 62 undergraduate students using the purposive sampling technique in 2-4 years nursing students. As a research instrument, the revised Olweus bully/victim questionnaire (OBVQ-R) was administered to students. The data were analysed using descriptive analysis in SPSS version 26.0. The data showed that there were 10 patterns of bullying performed and received by nursing students in this study. In the category of victimisation, the highest pattern performed was spread rumours/lies talk (48.4%), followed by mean names (37.1%). In the aggression scale that represents bullying, the most common complaints are